2019
DOI: 10.3389/fnagi.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Greek Traditional Dances: A Way to Support Intellectual, Psychological, and Motor Functions in Senior Citizens at Risk of Neurodegeneration

Abstract: One of the major problems that elderly people are facing is dementia. For scientist’s dementia is a medical, social and economic problem, as it has been characterized as the epidemic of the 21st century. Prevention and treatment in the initial stages of dementia are essential, and community awareness and specialization of health professionals are required, with the aim of early and valid diagnosis of the disease. Activities are recommended to the senior citizens to improve their physical and mental health. Dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…In our study, the analysis within the groups before and after the training showed that the active group improved in all the physical parameters (flexibility of low back and hamstrings, the functional capacity of individuals through the strength of the lower limbs and the dynamic balance, the speed, agility and balance during movement) under investigation, which is in line with previous studies [23] . On the contrary, the Passive group showed minor or no improvement at all.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the analysis within the groups before and after the training showed that the active group improved in all the physical parameters (flexibility of low back and hamstrings, the functional capacity of individuals through the strength of the lower limbs and the dynamic balance, the speed, agility and balance during movement) under investigation, which is in line with previous studies [23] . On the contrary, the Passive group showed minor or no improvement at all.…”
Section: Discussionsupporting
confidence: 91%
“…A funcionalidade, entendida como a interação entre várias dimensões (biológica, individual e social), é uma área chave que pode ser afetada pelo envelhecimento, e a falta de mobilidade é a principal razão pela qual os idosos têm problemas com a funcionalidade 26 .…”
Section: Discussionunclassified
“…Frente ao trabalho apresentado, evidencia-se que a dança ritmada praticada de forma regular, têm benefícios significativos como melhora do equilíbrio, a coordenação da marcha, mobilidade, estabilidade e consequentemente reduz o risco de quedas em idosos em relação aos idosos que o praticam de forma irregular. Além de oferecer benefícios psicológicos que podem tornar o exercício mais interessante e divertido, já que inclui múltiplas tarefas e música 26 , podendo influenciar até mesmo na qualidade de vida dessas pessoas.…”
Section: Discussionunclassified
“…Our approach to this study is scaffolded on simultaneous research involving groups of experts (break-dancers, ballet dancers, choreographers) who regularly engage in music-driven behaviors, such as associated or learned movements and states. Experts have putative specialized neural circuits for behaviors related to their area of expertise that can be probed for brain–behavior relationships [ 9 ] and potentially used in training to reduce neurodegeneration [ 10 , 11 ]. These brain–behavior associations can be further elaborated through a “first-person neuroscience” approach [ 12 ], correlating brain changes with the practitioner’s subjective experience.…”
Section: Introductionmentioning
confidence: 99%